2015
DOI: 10.1111/are.12927
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia nitrogen excretion in Mandarin Fish (Siniperca chuatsi) and Grass Carp (Ctenopharyngodon idellus) fed practical diets: the effects of water temperature

Abstract: To understand the actual production of fish culture about the utilization of dietary protein and excreta impact on the environment between mandarin fish (Siniperca chuatsi) and grass carp (Ctenopharyngodon idellus), the study to investigate the effect of temperatures (19 AE 0.5°C, 24 AE 0.5°C and 29 AE 0.5°C) on ammonia-N excretion in mandarin fish and grass carp under fed and fasted states was conducted. These two species were fed a practical diet containing 325.2 g kg À1 crude protein at 3% body weight per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The ammoniac is considered as the most toxic fraction of TAN that is defined by the sum of ammonium ion and ammoniac (EPA, 1998). The ammoniac effect is related to temperature, salinity, oxygen and pH (Randall and Tsui, 2002;Fang et al, 2017), on this basis, the temperature observed in the present study was, within the optimal tolerance level (Randall and Tsui, 2002), and whereas at salinity level at high NaCl concentration the ammoniac toxic effect is lower (Randall and Tsui, 2002;Rodrigues et al, 2007;Fang et al, 2017). Also, in increment condition of sodium and calcium in oxygen saturated water the ammoniac effect decreased (Foss et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…The ammoniac is considered as the most toxic fraction of TAN that is defined by the sum of ammonium ion and ammoniac (EPA, 1998). The ammoniac effect is related to temperature, salinity, oxygen and pH (Randall and Tsui, 2002;Fang et al, 2017), on this basis, the temperature observed in the present study was, within the optimal tolerance level (Randall and Tsui, 2002), and whereas at salinity level at high NaCl concentration the ammoniac toxic effect is lower (Randall and Tsui, 2002;Rodrigues et al, 2007;Fang et al, 2017). Also, in increment condition of sodium and calcium in oxygen saturated water the ammoniac effect decreased (Foss et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…The inclusion of a 27% of soybean and cotton hydrolysate mixture to replace fishmeal in Scophthalmus maximus diets increased the protein efficiency ratio (Song et al, 2018). Furthermore, enzymatic hydrolysis increases protein retention, which reduces environmental pollution caused by nitrogen compounds (Fang et al, 2017;Song et al, 2018;Song, Wang, Qiao, Zhang, & Li, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia is the basic end product of amino acid catabolism in freshwater fish (Fang et al, 2017) and TAN is a factor that restricts fish production in culture systems because of its toxicity (Cruz et al, 2013). Therefore, it can be used well-organized nutritional strategies to reduce TAN levels in fish systems without decreasing growth and reproductive performance or cost-effectiveness (Hardy & Gatlin, 2002).…”
Section: Discussionmentioning
confidence: 99%